5, 6‐bis(tetradecyloxy)‐2, 1, 3‐benzoselenadiazole‐based polymers for photovoltaic applications. Issue 6 (8th October 2012) - Tang, Wanjun; Chen, Xuewen; Zou, Yingping; Liu, Bo; Zhong, Hong; Pan, Chunyue
Abstract A series of new 5, 6‐bis(tetradecyloxy)‐2, 1, 3‐benzoselenadiazole‐based copolymers (PBDT‐DTBSe, PC‐DTBSe, and PF‐DTBSe) have been first synthesized by Stille or Suzuki coupling polymerization reaction. The synthesized copolymers show good solubility in common organic solvents, such as chloroform, tetrahydrofuran, and chlorobenzene with excellent film‐forming properties. The molecular weight was determined by gel permeation chromatography and the thermal properties were investigated by thermogravimetric analysis. All the copolymers exhibited broad absorption from 350 to 700 nm. The preliminary results showed the device based on the structure of indium tin oxide/PEDOT:PSS/PC‐DTBSe:PC61BM (1 : 2, w/w)/Ca/Al displayed the best photovoltaic performance with a power conversion efficiency of 1.35%, a Voc of 0.87 V, a Jsc of 3.84 mA/cm2 and a fill factor of 40.4%, under illumination of AM 1.5 G (100 mW/cm2). © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013